Corrigendum for: Patorani local knowledge system in fisheries resources conservation education in Galesong District South Sulawesi - Hasriyanti Hasriyanti; Rusdi Rusdi; Titus Adeyemi Alonge; Erman Syarif (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2023)
We sincerely express our apology for the changes in the author list in the article entitled Patorani local knowledge system in fisheries resources conservation education in Galesong District South Sulawesi. This article was published on DOI: 10.17977/um017v28i12023p52-63, with the authors list consisting of Hasriyanti, Rusdi, Alonge Titus Adeyemi, Michel E. D. Chaves, and Erman Syarif. However, Michel E. D. Chaves issue a complaint regarding his involvement during the research and paper completion. He did not agree to the inclusion of his name in the author list. We have contacted the corresponding author for confirmation. Besides, the co-author has also confirmed the mistake in the writing of one of the author’s names, Alonge Titus Adeyemi, which should be Titus Adeyemi Alonge. The corresponding author has submitted a letter of author contribution signed by Hasriyanti, Rusdi, Titus Adeyemi Alonge, and Erman Syarif. The original article has been revised, and reasonable effort should be made to remove all references to this article.